STRESS AND MENTAL HEALTH OF UNDERGRADUTE STUDENTS AT A PRIVATE HIGHER LEARNING INSTITUTION IN MALAYSIA - Othman, Mohd Azman; Rashid, Mas Anom (PEOPLE: International Journal of Social Sciences, 2018)
Malaysia has an uprising trend in mental health problem among tertiary level students based on statistics which shows there is an increase in the number cases registered from 2011 to 2016. Mental health problems among students are caused by anxiety and also depression and at same time the influence of drugs as a factor is also a possible plausible cause. Hence, this study was aimed to seek some confirmations to the statement and determine the overall state of the students’ mental health. Apart from that the study also wanted to single out what is the most influential factor that affects their mental health and how they manage these issues. A total of 350 respondents participated in this study and findings revealed that 50% of them suffered some kind of depressions triggered by various factors. It was found that the students do seek professional help available at the college to help them deal with their mental health issue. There was no significant different based on gender seeking help from the professional services provided even though it was reported that each experiencing different kind problem. From the academic aspect on the other hand, program enrolled and the semester they are in do not pose any problem to the respondents.